Comparison of the Origin and Development of the Phraseological Units ločiti ljuljko od pšenice ‘to separate the tares from the wheat’ and ločiti zrnje od plev ‘to separate the grain from the chaff’ and Their Variants in Literary Slovenian - Trivunović, Eva (Jezikoslovni zapiski, 2023)
This paper presents the origin of two phraseological units derived from the Bible ločiti ljuljko od pšenice ‘to separate tares/weed from the wheat’ and ločiti zrnje od plev ‘to separate the wheat from the chaff’ and their development in standard Slovenian from the 16th century to modern times. The two have many similarities, but were used very differently. In 16th century standard Slovenian the image of tares between wheat was more frequent than ločiti zrnje od plev, although not in the same form as the modern phraseological unit. But as time passed phraseological unit ločiti zrnje od plev and its many variants became more prominent, which is supported by its presence in dictionaries and corporal analysis.